Occupational health and safety among Airline crew members(Pilots and Cabin crew) in Nepal. - Thapa, Sheela (2021)
SUMMARY: Occupational Health and Safety in the workplace is a global issue. High morbidity and mortality due to Work-related events in developing countries is a major cause of poverty affecting families, communities, and the nation as a whole. This study aimed to assess the present health problems and assess their knowledge towards occupational health and safety. A cross-sectional study design was used among 141 pilots and cabin crew of different airlines through email. The respondents were selected using the census method. The Occupational Safety and Health vulnerability tool along with a self-developed knowledge assessment tool was used to collect data. The data was analyzed in SPSS 16. The univariate analysis was performed on recommended variables. Based on findings, nearly about three- fourth of the respondents were male, and about 65% of the respondents belonged to the age group of 26 to 35. The current residence of 95.7% was in Bagmati Province. Married respondents in the survey were 56.7%. Most of the respondents (84.4%) belonged to the Hindu religion and majority of the ethnicity was Brahmin/ Chettri (56.7%). The educational status of the majority of the respondents was Bachelor (44.7%) and Intermediate (34.8%). Among the respondents 138 were in active status and 3 were inactive in the profession. Nearly three-fifth (73.8%) were involved in the private agency. Majority (57.6%) were flying the international airlines and one-tenth were flying both international and domestic airlines. Similarly, 56.7% of respondents were working as pilots. Similarly, 41.8% of respondents' total employment year of 1-5. More than half (53.9%) had total flight hours of 1000-5000 and 58.2% had worked a total flight of more than 250 hours in the last six month. Majority (95.7%) mentioned that their company had institutional policies on safety measures. More than half (56.7%) of the respondents had vigorous intensity activities for at least 10 minutes continuously. 73.8% were involved in moderate intensity activities. the majority 85.1% had done regular medical checkup. 82.3% had rated their health status as good. BMI of 23.4 % was more than normal weight. 68.1 % do not smoke currently. 84.4% of respondents had ever consumed an alcoholic drink. Almost two tenth (39.7%) of crew members had a moderate level of knowledge and 28.4% had a poor level of knowledge regarding occupational health and safety. The overall prevalence of OHS vulnerability among the pilots and cabin crew was calculated to be 100% as per the occupational safety and health vulnerability measure scale. All the respondents faced the workplace hazards as their occupation was always required to work at above more than 2 meters from the ground level. As per the same scale, 39% of respondents had inadequate access to workplace policies and procedures. Only 10.63% of respondents had inadequate awareness of hazards and OHS rights and responsibilities. The number of participants who had inadequate empowerment to participate in injury and illness prevention was 36.1%.